The effects of supplementary feeding and weather factors on the breeding success of Osprey, Pandion haliaetus, in Finland - Sivonen, Tero (Helsingfors universitet, 2014)
Osprey Pandion haliaetus has been under a strict surveillance of the nature conservationists and a conservation icon since the early 70’s. At that time the accumulation of persistent environmental toxins and pollutants lowered the populations of many birds of prey to low levels, threatening the survival of entire species. Nowadays osprey is one of the successful models of endangered species protection. Because of its status osprey is very thoroughly studied raptor. Due to environmental toxins many birds of prey suffered from eggshell thinning and lost clutches till the end of 1970’s. Eggshell thinning has later stopped and is now reverting, but after the start of intense studying of the birds other threats have been observed to reduce reproductive success. Many earlier studies have suggested that extreme weather conditions may have an effect on the nesting success of diurnal birds of prey. In osprey´s case many researchers have examined the effects of different weather patterns to foraging success and food delivery, but a specific review over their effects on the nesting success hasn’t been conducted so far. In this study I focus on the effects of different weather factors and their contemporary nesting success. I study a nature conservation based supplementary feeding pond‘s effect to the local osprey population’s reproductive success, combined with the weather variables and the density of nesting pairs. Osprey is recorded to fly approximately 3–15 km on its foraging trips. At their longest these fishing trips can be over 40 km long one-way. The Osprey Center, working in Pohtiolampi at Kangasala (61° 26.876' N, 24° 7.705' E), in Southern Finland, feeds the local ospreys with living rainbow trout from an old fish farm pool. In theory, the birds nesting or living near the supplementary feeding pond benefit from this in a form of easy sustenance. The fish move near the water surface and are thus available all the time. Especially during bad weather conditions the pond is frequently visited by nesting ospreys. In ...